Integrasi Program Tahfiz dan Bilingual sebagai Mekanisme Pengembangan Sekolah Unggul di MTSN 8 Jombang - Sriati, Sriati; Ashari, M. Yahya (TSAQOFAH, 2026)
The integration of the Tahfiz Program and the Bilingual Program at MTsN 8 Jombang has been developed as a strategy to strengthen academic quality, spirituality, and global competence through the management of integrated flagship programs. This study aimed to analyze the planning, implementation, and management of the integration of the two programs, as well as to identify supporting and inhibiting factors in its implementation. A qualitative approach with a case study design was employed, with data obtained through interviews, observations, and documentation, and analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The findings show that the integration of the Tahfiz Program and the Bilingual Program is carried out through curriculum alignment, teacher collaboration, the strengthening of a Qur’an-based school culture, language-based learning, and systematic evaluation. The Tahfiz Program contributes to the formation of students’ religious character, discipline, and spirituality, whereas the Bilingual Program enhances students’ global communication skills and language literacy. In conclusion, the integration of the two programs has been proven to strengthen the quality of learning while consolidating the madrasah’s identity as an excellent school that is religious, modern, and globally oriented.